Product and Institutional Development of Gambier Agricultural Markets in Rural Indonesia: A Case Study of Nagari Pangkalan, Sumatra Barat Province - Nasrul, Wedy; Suwita, Leli; Ernanda, Revi; Ramadhan, Fajri (Sodality: Jurnal Sosiologi Pedesaan, 2024)
Gambier is a speciality agricultural product in Sumatra Barat Province, Indonesia. Gambier farming has improved the community economy and rural development. The problem is that the gambier products produced are still raw materials, the quality is low, and the market for gambier is not perfect. So far, there have been no real solutions and policies from stakeholders to overcome these problems. This study aims to find solutions in product development and institutional improvement of the gambier market. This research uses a qualitative method. The case study is in Nagari Pangkalan, one of the centres of gambier farming in Sumatra Barat. The results showed that it is important to develop gambier products in the form of catechins and tannins in Nagari Pangkalan. The high price of catechins and tannins can increase farmers' income. It is necessary to build a gambier agribusiness centre by involving farmer groups, cooperatives and the government in Nagari Pangkalan. The Gambier Agribusiness Centre will reduce the dominance of gatherers and increase the role of cooperatives in the gambier market. The government designs regulations related to gambier exports by involving cooperatives. The export of gambier through cooperatives will shorten the marketing flow of gambier and benefit gambier farmers more. A gambier market that benefits farmers will indirectly help the economy and rural development.